Roles of mobile phone in increasing productivity of Malaysian agro-based entrepreneur - Mohamed Shaffril, Hayrol Azril; Hassan, Md. Salleh (Medwell Online, 2012)
Mobile phone and agriculture are two different things that can be integrated in so many ways. As other industries are manipulating the advantages of mobile phone so do the agriculture industry. The main objective of this study is to investigate the various purpose of mobile phone usage among the agro-entrepenuers while unleashing the contribution of this tool towards agro-based entreprenuers productivity. Apart from this, this study would like to discover any impacts of mobile phone usage on agro-entreprenuers productivity. This is a quantitative study where a developed instrument was used. A total of 365 respondents across Peninsular Malaysia were surveyed to gain the required data. Majority of the agro-based entreprenuers use mobile phone for seeking information related to their business activities while mobile phone has contributed towards their productivity in term of getting information needed and widening their networkings. Further analysis using independent t-test has confirmed that there was no significant difference in productivitiy for those who use mobile phone frequently and seldomly. It is recommended that responsible agencies such as Department of Agriculture and Malaysia and Communication and Multimedia Commission should play their role in promoting the advantages that mobile phone has in increasing agricultural productivity. Mobile web and phone line specifically for agriculture information should be created in doubling the function of mobile phone in agriculture.